High field magneto-transport of mixed topological insulators Bi2Se3-xTex (x = 0, 1, 2 & 3). (January 2021) - Sharma, Deepak; Kumar, Yogesh; Kumar, P.; Nagpal, V.; Patnaik, S.; Awana, V.P.S.
Abstract: The article comprises structural, microstructural, and physical properties analysis of Bi2 Se3-x Tex (x = 0, 1, 2 & 3) mixed topological insulator (MTI) single crystals. All the crystals were grown through a well-optimized solid-state reaction route via the self-flux method. These MTI are well characterized through XRD (X-ray Diffractometer), SEM (Scanning Electron Microscopy), EDAX (Energy Dispersive Spectroscopy), and thereby, the physical properties are analyzed through the RT (Resistance vs temperature) down to 10 K as well as the magneto-resistance (MR) measurements (at 5 K) in a magnetic field of up to ± 10 T. The MR% drastically varies from x = 0 to x = 3 in MTI, from a huge 400%, it goes down to 20% and 5% and eventually back to 315%. This fascinated behavior of MR is explained in this article through HLN (Hikami-Larkin-Nagaoka equation) and an additional term. This article not only proposed the mesmerizing behavior of MR in MTI but also explains the reason through competing WAL (Weak Anti-Localization) and WL (Weak Localization) conduction processes. Highlights: Bi2(Se3-xTex): x = 0 to 3 MTI crystals are grown through a well-optimized solid-state reaction route via the self-flux method. MR is measured at 5K in fields up to 10Tesla. MR% decreases from huge 400% to 20% for mixed TI. The fadcinating MR is explained on basis of HLN and competing WAL and WL processes.